CompTIA Cloud Essentials+ Study Guide, 2nd Edition - Docter, Quentin; Fuchs, Cory (Sybex, 2020)
Prepare for success on the New Cloud Essentials+ Exam (CLO-002) The latest title in the popular Sybex Study Guide series, CompTIA Cloud Essentials+ Study Guide helps candidates prepare for taking the NEW CompTIA Cloud Essentials+ Exam (CLO-002). Ideal for non-technical professionals in IT environments, such as marketers, sales people, and business analysts, this guide introduces cloud technologies at a foundational level. This book is also an excellent resource for those with little previous knowledge of cloud computing who are looking to start their careers as cloud administrators. The book covers all the topics needed to succeed on the Cloud Essentials+ exam and provides knowledge and skills that any cloud computing professional will need to be familiar with. This skill set is in high demand, and excellent careers await in the field of cloud computing. Gets you up to speed on fundamental cloud computing concepts and technologies Prepares IT professionals and those new to the cloud for the CompTIA Cloud Essentials+ exam objectives Provides practical information on making decisions about cloud technologies and their business impact Helps candidates evaluate business use cases, financial impacts, cloud technologies, and deployment models Examines various models for cloud computing implementation, including public and private clouds Identifies strategies for implementation on tight budgets Inside is everything candidates need to know about cloud concepts, the business principles of cloud environments, management and technical operations, cloud security, and more. Readers will also have access to Sybex's superior online interactive learning environment and test bank, including chapter tests, practice exams, electronic flashcards, and a glossary of key terms.